The Use of Augmented Reality (AR) and Virtual Reality (VR) in Practical Education of Islamic Jurisprudence (Fiqh) - Alimohammad Heydarsarlak (پژوهش‌های فقهی مسائل مستحدثه)
Practical education of Islamic jurisprudence (fiqh) faces numerous challenges, including limitations in time, space, and educational resources. This research examines the potential of using Augmented Reality (AR) and Virtual Reality (VR) technologies to enhance the quality of practical education in Islamic jurisprudence. The main objective is to analyze the possibilities and challenges of implementing these technologies in the field of fiqh education and to provide strategies for their effective utilization. This study was conducted using library research and analytical methods. The sources used include books, scientific articles, and research reports in the fields of educational technology, AR and VR, and religious education. The research findings indicate that AR and VR have significant potential to revolutionize the practical education of Islamic jurisprudence. These technologies can improve learners’ understanding and learning by creating simulated environments, providing interactive experiences, and enabling practice in virtual spaces. Additionally, the use of these technologies can help increase student motivation and active participation. However, challenges such as the need for technical infrastructure, teacher training, and adapting educational content to these technologies have also been identified. This research, by providing strategies for the successful implementation of AR and VR in fiqh education, paves the way for future empirical studies in this field.